Biochemical reaction kinetics of acetone-butanol-ethanol (ABE) fermentation of pineapple waste hydrolysate in coupled fermentation-pervaporation system - Nguyen, Thien-Phuc (Animo Repository, 2018)
In this study, from pineapple waste hydrolysate, butanol production by using Clostridium Acetobutylicum as microorganism, and coupled fermentation-pervaporation setup as Acetone-Butanol-Ethanol (ABE) fermentation reactor was investigated with respect to biochemical reaction kinetics and butanol yield. Production of butanol by fermentation was done by both in fermenter only and in coupled fermentation-pervaporation reaction systems. For fermenter only, kinetics and effect of temperature at 35°C and 40°C were examined. Higher fermentation temperature resulted in lower butanol yield possibly due to the change in cell membrane fluidity. Besides, fermentation behaviour was simulated by using modified Eom’s kinetics with butanol as an inhibitor. The raw data was fitted to different biochemical reaction kinetic models to determine its kinetic parameters. Results of simulation from MATLAB using modified Eom’s model showed high accuracy of fitting with R2 higher than 0.92. Subsequently, pervaporation system using polydimethylsiloxane (PDMS) membrane was integrated into the fermentation system to investigate the simultaneous separation of butanol from fermentation broth. The effect of temperature and circulation flowrate on butanol permeate flux, separation factor, and butanol yield was also investigated. the Higher temperature and circulation enhanced butanol flux, but overall butanol yield was lower as higher temperature affected negatively the fermentation process. Nevertheless, the coupled system still produced more butanol compared to fermenter only, with 28.87% increase of butanol yield from the best combination at 35°C and 0.15 L/min. Compared to fermenter only, the application of pervaporation into the fermenter allowed 10 times higher butanol concentration in the permeate mixture, which was clear and almost free of biomass. Additionally, kinetics of the coupled system was analysed, and under the effect of pervaporation, higher butanol tolerance was achievable with 4 times higher, interpreted from kinetic parameters. The kinetic model of the coupled system also showed good data fitting with R2 higher than 0.81. Overall, it can be concluded that the coupled system has great potential for ABE fermentation, and the study of its biochemical kinetics can be useful for process design and optimization.